Non-O1Vibrio cholerae bacteremia in an infant, first case report from Pakistan - Samreen Sarwar; Abdul Hannan; Qamar Sultana; Sidrah Saleem; Muhammad Sohail; Muhammad Usman Arshad; Karam Rasool (Journal of Infection in Developing Countries)
To the best of our knowledge, Non-O1 Vibrio cholerae (NOVC) bacteremia has never been documented in Pakistan. This case report is the first reported case of bacteremia in an infant due to NOVC in Pakistan. A neonate was admitted to a hospital with fever and no history of diarrhea. The isolate was identified biochemically and serologically and was sensitive to all the drugs tested as per CLSI 2014 guidelines.